Gastrointestinal involvement in POEMS syndrome: a novel clinical manifestation. Issue 959 (2nd September 2005) - Dogan, S; Beyazit, Y; Shorbagi, A; Köklü, S; Ustunel, S; Guler, N; Uner, A
Abstract : POEMS syndrome (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes) is characterised by a rare multisystem disorder of unknown pathogenesis. Although its pathophysiology is not well understood, overexpression of proinflammatory cytokines has been implicated. Gastrointestinal system disorders have not been reported among the components of the syndrome. A case is reported of POEMS syndrome with gastrointestinal involvement shown by gastrointestinal endoscopy.